Spontaneous calf haematoma: case report - Nor Hanipah, Zubaidah; Liew, Ngoh Chin (Malaysian Medical Association, 2014)
Spontaneous calf haematoma is a rare condition and few case reports have been published in the English literature. Common conditions like deep vein thrombosis and traumatic gastrocnemius muscle tear need to be considered when a patient presents with unilateral calf swelling and tenderness. Ultrasound and Magnetic Resonance Imaging are essential for confirmation of diagnosis. The purpose of this paper is to report on a rare case of spontaneous calf hematoma and its diagnosis and management.